Cathode active material for lithium secondary battery, preparing method thereof, cathode for lithium secondary battery including the same, and lithium secondary battery comprising cathode including the same
Patent Information
- Application Number
- KR1020250112548
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-08-13
- Publication Date
- 2026-09-21
- Estimated Expiration
- 2043-03-24
Smart Images

Figure 112025092499239-PAT00009_ABST
Abstract
Description
Technology Field
[0001] The invention relates to a positive electrode active material for a lithium secondary battery, a method for manufacturing the same, a positive electrode for a lithium secondary battery including the same, and a lithium secondary battery. Background Technology
[0002] With the advancement of portable electronic and communication devices, there is a growing need for the development of high-energy-density lithium-ion batteries. However, high-energy-density lithium-ion batteries can compromise safety, necessitating improvements in this area.
[0003] In order to manufacture lithium secondary batteries with long lifespan and reduced gas, the use of single-crystal cathode active materials is being considered as the cathode active material for lithium secondary batteries. However, single-crystal cathode active materials have problems such as particle aggregation or reduced productivity due to heat treatment at high temperatures for single crystallization.
[0004] Single-crystal cathode active materials exhibit relatively lower discharge capacity and charge / discharge efficiency compared to polycrystalline cathode active materials, so improvement is required in this regard. The problem to be solved
[0005] One aspect is to provide a novel cathode active material for lithium secondary batteries.
[0006] Another aspect is the method for manufacturing the anode active material described above.
[0007] Another aspect is that a positive electrode containing the aforementioned positive electrode active material is provided, with improved discharge capacity and charge / discharge efficiency.
[0008] Another aspect is that a lithium secondary battery including the aforementioned positive electrode is provided. means of solving the problem
[0009] Depending on one aspect
[0010] It is a nickel-based lithium metal oxide single particle, and
[0011] The size of the above single particle is 1 to 4 μm, and
[0012] A positive electrode active material for a lithium secondary battery is provided, comprising a coating layer containing a cobalt compound disposed on the surface of the nickel-based lithium metal oxide single particle, wherein the nickel-based lithium metal oxide single particle is doped with molybdenum.
[0013] The molybdenum content is 0.1 mol% or more and less than 1.0 mol% based on 100 mol% of the total metal content excluding lithium in the positive electrode active material. In addition, the cobalt compound content in the cobalt compound-containing coating layer is 0.1 to 5.0 mol% based on the total content of the positive electrode active material, and the thickness of the cobalt compound-containing coating layer is 1 nm to 50 nm.
[0014] In the above-mentioned cobalt compound-containing coating layer, the cobalt compound-containing compound is cobalt oxide, lithium cobalt oxide, or a combination thereof. Furthermore, the above-mentioned cobalt compound-containing coating layer further comprises one or more selected from boron, manganese, phosphorus, aluminum, zinc, zirconium, and titanium.
[0015] The above nickel-based lithium metal oxide is a compound represented by the following chemical formula 1.
[0016] [Chemical Formula 1]
[0017] Li a (Ni 1-x-y M1 x M2 y )O 2±α1
[0018] In Chemical Formula 1, M1 is one or more elements selected from Co, Mn and Al, and
[0019] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0020] 0.95≤a≤1.1, 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, 0≤α1≤0.1, and cases where x and y are both 0 are excluded.
[0021] The above nickel-based lithium metal oxide is a compound represented by the following chemical formula 2.
[0022] [Chemical Formula 2]
[0023] Li a (Ni 1-x-y-z Co x M3 y M4 z )O 2±α1
[0024] In Chemical Formula 2, M3 is one or more elements selected from Mn and Al, and
[0025] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0026] 0.95≤a≤1.1, 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, 0≤α1≤0.1, and cases where x, y and z are simultaneously 0 are excluded.
[0027] FWHM measured by X-ray diffraction analysis of the above positive electrode active material (003) / FWHM (104) It is 0.72 to 0.79.
[0028] A step of obtaining a mixture by mixing a nickel precursor, one or more selected from M1 precursors and M2 precursors according to another aspect, and a basic solution, and then performing a co-precipitation reaction of the mixture, and then drying the mixture to obtain a nickel-based metal precursor having internal pores;
[0029] A step of obtaining a mixture of a nickel-based metal precursor having internal pores and a lithium precursor;
[0030] A step of adding a molybdenum precursor to the above mixture and performing a first heat treatment of the obtained mixture;
[0031] A step of performing a grinding process on the product that has undergone primary heat treatment;
[0032] The above-described positive active material is manufactured by including the step of adding a cobalt precursor to the above product to obtain a mixture, and performing a secondary heat treatment on the mixture.
[0033] The above first heat treatment is performed at a higher temperature than the second heat treatment, and
[0034] The above M1 precursor is one or more selected from cobalt precursors, manganese precursors, and aluminum precursors, and
[0035] A method for manufacturing a positive electrode active material for a lithium secondary battery is provided, wherein the above M2 precursor is a precursor containing one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr).
[0036] The size of the internal pore region in the above nickel-based metal precursor is 2 to 7 μm, and the cobalt precursor is Co(OH)2, CoOOH, CoO, Co2O3, Co3O4, Co(OCOCH3)2·4H2O, CoCl2, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or a combination thereof.
[0037] The above nickel-based metal precursor is a compound represented by the following chemical formula 3, a compound represented by chemical formula 4, or a combination thereof.
[0038] [Chemical Formula 3]
[0039] (Ni 1-x-y M1 x M2 y )(OH)2
[0040] In Chemical Formula 3, M1 is one or more elements selected from Co, Mn and Al, and
[0041] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0042] 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, cases where x and y are both 0 are excluded, and
[0043] [Chemical Formula 4]
[0044] (Ni 1-x-y M1 x M2 y )O
[0045] In Chemical Formula 4, M1 is one or more elements selected from Co, Mn and Al, and
[0046] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0047] 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, and cases where x and y are both 0 are excluded.
[0048] The above nickel-based metal precursor is represented by a compound of Chemical Formula 5, a compound of Chemical Formula 6, or a combination thereof.
[0049] [Chemical Formula 5]
[0050] Ni 1-x-y-z Co x M3 y M4 z (OH)2
[0051] In Chemical Formula 5, M3 is one or more elements selected from Mn and Al, and
[0052] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0053] 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y, and z are simultaneously 0 are excluded, and
[0054] [Chemical Formula 6]
[0055] (Ni 1-x-y-z Co x M3 y M4 z )O
[0056] In Chemical Formula 6, M3 is one or more elements selected from Mn and Al, and
[0057] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0058] 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y and z are simultaneously 0 are excluded.
[0059] The nickel-based metal precursor and the lithium precursor are mixed such that the Li / Me (metal excluding Li) molar ratio is 0.9 or more and less than 1.1, and the lithium precursor is lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, or a combination thereof.
[0060] The above first heat treatment is carried out in an oxidizing gas atmosphere at 800°C to 1200°C, and the above second heat treatment is carried out in an oxidizing gas atmosphere at 600°C to 850°C.
[0061] According to another aspect, a positive electrode for a lithium secondary battery comprising a positive current collector and a positive active material layer disposed on the positive current collector, and
[0062] The above-described positive active material layer is provided as a positive electrode for a lithium secondary battery comprising the above-described positive active material.
[0063] According to another aspect, a lithium secondary battery comprising the anode, cathode, and electrolyte interposed between them as described above is provided. Effects of the invention
[0064] By using a cathode active material for a lithium secondary battery according to one aspect, it is possible to manufacture a nickel-based active material for a lithium secondary battery with improved capacity characteristics, which suppresses inter-particle aggregation, enhances productivity, and reduces the cation mixing ratio. A lithium secondary battery manufactured using such a nickel-based active material for a lithium secondary battery exhibits improved discharge capacity and charge / discharge efficiency. Brief explanation of the drawing
[0065] FIG. 1a schematically shows the cross-sectional structure of a product having a one-layer structure obtained after a first heat treatment when manufacturing an anode active material according to one embodiment. FIG. 1b schematically shows the cross-sectional structure of a product having a two-layer structure obtained after a first heat treatment when manufacturing an anode active material according to another embodiment. Figure 1c is a scanning electron microscope image showing the cross-sectional structure of the product obtained after the first heat treatment during the preparation of the positive electrode active material according to Example 1. Figures 2a to 2c are scanning electron microscope images of the surface of the primary heat treatment product during the preparation of the positive electrode active material of Example 1. Figures 2d and 2e are scanning electron microscope images of the surface of the positive electrode active material of Example 1. Figures 3a to 3c are scanning electron microscope images of the surface of the primary heat treatment product during the preparation of the positive electrode active material of Example 2. Figures 3d and 3e are scanning electron microscope images of the surface of the positive electrode active material of Example 2. Figures 4a to 4c are scanning electron microscope images of the surface of the primary heat treatment product during the preparation of the positive electrode active material of Example 3. Figures 4d and 4e are scanning electron microscope images of the surface of the positive electrode active material of Example 3. Figures 5a to 5c are scanning electron microscope images of the surface of the primary heat treatment product during the preparation of the positive electrode active material of Reference Example 1. Figures 5d and 5e are scanning electron microscope images of the surface of the positive electrode active material of Reference Example 2. Figure 6 is an electron microscope image showing the cross-sectional structure of the positive electrode active material obtained according to Preparation Example 1, based on the scanning electron microscope analysis of the nickel-based metal precursor of Preparation Example 1. Figure 7 is a graph showing the particle size distribution characteristics in the positive active materials of Examples 1 to 3 and Reference Example 1. FIG. 8a shows the change in voltage capacity according to voltage in the coin cells of Manufacturing Examples 1 to 3, Reference Manufacturing Example 1, and Reference Manufacturing Example 2. FIG. 8b shows the change in resistance that occurs during charging in the coin cells of Manufacturing Examples 1 to 3, Reference Manufacturing Example 1, and Reference Manufacturing Example 2. Figure 9 is a graph showing the capacity retention rate characteristics in the coin cells of Production Examples 1 to 3, Reference Production Example 1, and Reference Production Example 2. FIG. 10 is a schematic diagram of a lithium secondary battery according to an exemplary embodiment. Specific details for implementing the invention
[0066] Hereinafter, a positive electrode active material for a lithium secondary battery according to one embodiment, a method for manufacturing the same, a positive electrode including the same, and a lithium secondary battery equipped with said positive electrode will be described in detail.
[0067] In order to manufacture lithium secondary batteries with improved lifespan characteristics, a cathode containing a single-crystal cathode active material is used. During the manufacturing process of single-crystal cathode active materials, an excess amount of lithium is added and subjected to high-temperature heat treatment; however, due to this high-temperature heat treatment, particles clump together, productivity decreases, and residual lithium increases. Furthermore, when lithium secondary batteries are manufactured using such single-crystal cathode active materials, the capacity and charge / discharge efficiency decrease.
[0068] Single-crystal cathode active materials exhibit particle aggregation, requiring a grinding process during cathode manufacturing. However, when conventional single-crystal cathode active materials undergo this grinding process, their single-crystal characteristics deteriorate, residual ground matter is generated, and surface resistance is high.
[0069] Accordingly, the inventors have solved the aforementioned problems and completed the present invention regarding a positive electrode active material in which the crystallinity of the positive electrode active material is reduced or surface defects are hardly generated after a secondary heat treatment even when a grinding process is performed, thereby improving surface resistance characteristics.
[0070] The positive electrode active material for a lithium secondary battery according to one embodiment is a nickel-based lithium metal oxide single particle, and
[0071] The size of the above single particle is 1 to 4 μm, and
[0072] It comprises a cobalt compound-containing coating layer disposed on the surface of the above-mentioned nickel-based lithium metal oxide single particle, and
[0073] The above nickel-based lithium metal oxide single particles are doped with molybdenum.
[0074] In this specification, a onebody (monolith, or monolithic particle) refers to a structure in which particles exist as independent phases that are not mutually aggregated in terms of morphology, and the particle size is 1 to 4 μm, for example, 2 to 4 μm. In this specification, the onebody has improved structural and morphological stability and is capable of mass production. Furthermore, by using a cathode containing such a cathode active material, it is possible to manufacture a lithium secondary battery with improved safety, capacity, and charge / discharge efficiency.
[0075] In this specification, if the particle is spherical, "size" indicates the average particle diameter, and if it is non-spherical, it indicates the average major axis length.
[0076] Particle size can be measured using a scanning electron microscope or a particle size analyzer. Examples of particle size analyzers include the HORIBA and LA-950 laser particle size analyzers. When measuring particle size using a particle size analyzer, the average particle diameter is referred to as D50. D50 refers to the average diameter of particles corresponding to a cumulative volume of 50% in the particle size distribution. In a distribution curve where particles are accumulated in order from the smallest to the largest, it represents the value of the particle diameter corresponding to 50% of the smallest particles when the total number of particles is set to 100%.
[0077] When measuring particle size using a scanning electron microscope, it is determined as the average value of at least 30 randomly selected particles of 1 μm or larger, excluding fine particles.
[0078] The average particle size of the above-mentioned positive electrode active material can be measured, for example, using a laser diffraction method. More specifically, after dispersing the above-mentioned positive electrode active material in a solution, it can be introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000) and irradiated with ultrasound of approximately 28 kHz at an output of 60 W, and then the average particle size (D50) at the 50% reference of the particle size distribution in the measuring device can be calculated.
[0079] In this specification, the term "D10" means the average diameter of a particle corresponding to 10 volume% of the cumulative volume in the particle size distribution, and "D90" means the average diameter of a particle corresponding to 90 volume% of the cumulative volume in the particle size distribution.
[0080] The particle size distribution (span) is expressed as (D90-D10) / D50. The particle size distribution is, for example, 0.9 to 1.5, 0.95 to 1.4, 0.98 to 1.2, or 0.98 to 1.1.
[0081] D90 is 4 to 7 μm, and D10 is 1.2 to 2.0 μm. D50 is 2 to 4 μm. When D90, D10, and D50 of the cathode active material are within the above ranges, the dispersibility between the cathode active materials is excellent and the specific surface area is appropriately maintained, resulting in excellent activity.
[0082] If the positive electrode active material includes a coating layer containing a cobalt compound, the surface resistance characteristics are improved, and a lithium secondary battery equipped with a positive electrode utilizing this improves the lifespan characteristics.
[0083] In this specification, a monolithic particle may be a particle containing one or more single crystals. A monolithic particle may be a particle containing a single crystal or several crystals.
[0084] In this specification, a single particle refers to a single particle (one body particle) having a primary particle size of 1 to 4 μm, and contains, for example, 1 to 3 particles.
[0085] In the positive active material according to one embodiment, the size of a single particle is, for example, 1 to 4 μm, 2 to 4 μm, or 2 to 3.5 μm. When the size of the single particle of the positive active material is within the above range, a positive active material with excellent capacity characteristics can be obtained.
[0086] In this specification, the term "interior" of the cathode active material refers to the area of 50 to 70 volume%, for example 60 volume%, from the center of the cathode active material, of the total volume from the center to the surface of the cathode active material, or the remaining area excluding the area within 3 μm from the outermost edge of the cathode active material (exterior) of the total distance from the center to the surface of the cathode active material.
[0087] The content of doped molybdenum in the positive electrode active material according to one embodiment is 0.1 mol% or more and less than 1 mol%, 0.1 to 0.5 mol%, or 0.1 to 0.4 mol% based on 100 mol% of the total metal content excluding lithium in the positive electrode active material. When the molybdenum content is within the above range, a positive electrode active material with improved lifespan characteristics and improved capacity and efficiency characteristics can be obtained.
[0088] The coating layer containing a cobalt compound can coat all or part of the surface of the positive electrode active material. For example, the coating layer can coat 90% or less, 80% or less, 70% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 1 to 10% of the surface of the positive electrode active material.
[0089] The content of the cobalt compound in the coating layer is 0.1 to 5.0 mol%, 0.5 to 5.0 mol%, 1 to 4 mol%, or 1.5 to 3 mol% based on the total content of the cathode active material (100 mol%). When the content of the cobalt compound falls within the above range, Ni present in large quantities in the metal layer during the synthesis process of the cathode active material 3+ ul Ni 2+ Lo, Co 4+ eu Co 3+ / Co 2+ By simultaneously reducing one or two types of ions, the reactivity between the interface of the positive active material and the electrolyte can be reduced.
[0090] The above-mentioned cobalt compound-containing coating layer comprises cobalt oxide, lithium cobalt oxide, or a combination thereof. Additionally, the cobalt-containing coating layer may further comprise one or more selected from boron, manganese, phosphorus, aluminum, zinc, zirconium, and titanium.
[0091] The thickness of the coating layer is 1 to 50 nm, 5 to 45 nm, or 10 to 35 nm. When the thickness of the coating layer is within the above range, a positive electrode active material with improved surface resistance characteristics can be obtained.
[0092] Nickel-based lithium metal oxide is a compound represented by the following chemical formula 1.
[0093] [Chemical Formula 1]
[0094] Li a (Ni 1-x-y M1 x M2 y )O 2±α1
[0095] In Chemical Formula 1, M1 is one or more elements selected from Co, Mn and Al, and
[0096] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0097] 0.95≤a≤1.1, 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, 0≤α1≤0.1, and cases where x and y are both 0 are excluded.
[0098] Nickel-based lithium metal oxides are compounds represented by, for example, Chemical Formula 2 below.
[0099] [Chemical Formula 2]
[0100] Li a (Ni 1-x-y-z Co x M3 y M4 z )O 2±α1
[0101] M3 is one or more elements selected from Mn and Al, and
[0102] In Chemical Formula 2, M3 is one or more elements selected from Mn and Al, and
[0103] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0104] 0.95≤a≤1.1, 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, 0≤α1≤0.1, and cases where x, y and z are simultaneously 0 are excluded.
[0105] FWHM of the positive electrode active material measured by X-ray diffraction analysis using Cu Kα radiation (1.54056 Å) according to one embodiment (003) / FWHM (104) The value is 0.72 to 0.79, or 0.73 to 0.77. When the above half-expand ratio is within the above range, the stability of the crystal structure of the positive active material can be improved.
[0106] The positive active material of the present invention is FWHM(003) This is 0.089° to 0.094°, 0.0895° to 0.093°, for example 0.0897° to 0.0910°, and FWHM (104) This is 0.11° to 0.13°, 0.115° to 0.125°, for example, 0.1198° to 0.1226°. Here, FWHM (003) represents the full width at half maximum (FWHM) of the peak corresponding to the (003) plane, and FWHM (104) represents the full width at half maximum of the peak corresponding to the (104) plane. FWHM (003) / FWHM (104) is a parameter created to evaluate the degree of uniform orientation (orientation) of the crystal grains.
[0107] In addition, the cathode active material according to one embodiment can be identified as being in a single-particle state by confirming grains and grain boundaries larger than the sub-micro scale when observing the cross-sectional microstructure through a scanning electron microscope.
[0108] FWHM of the above positive active material and the electrode plate including the positive active material (003) / FWHM (104) It has the same numerical range as the cathode active material. FWHM (003) / FWHM (104) When each of the above ranges is within the specified range, the stability of the crystal structure of the positive electrode active material is improved, and the expansion and contraction rates due to lithium absorption / release can be improved. Therefore, the capacity characteristics and charge / discharge efficiency of the battery can be improved.
[0109] Hereinafter, we will examine a method for manufacturing a positive electrode active material according to one embodiment.
[0110] First, a mixture obtained by mixing a nickel precursor, one or more metal precursors selected from M1 precursor and M2 precursor, and a basic solution is subjected to a co-precipitation reaction, and then dried to obtain a nickel-based metal precursor having internal pores. The nickel-based metal precursor has amorphous characteristics.
[0111] The above M1 precursor is identical to M1 of Chemical Formula 1 and is one or more selected from cobalt precursor, manganese precursor, and aluminum precursor. The above M2 precursor is identical to M2 of Chemical Formula 1 and is a precursor containing one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr).
[0112] The above metal precursor may include, for example, one or more selected from nickel precursor, cobalt precursor, manganese precursor and metal (M2) precursor.
[0113] During the above co-precipitation reaction, the pH of the mixture is controlled in two stages. The first stage is the pore formation stage, during which the pH of the mixture is controlled to 11.5 to 12. The second stage is the particle growth stage, during which the pH of the mixture is controlled to, for example, 10.5 to 11.9. The second stage is carried out at a lower pH than that of the first stage. By varying the co-precipitation rate in this manner, a difference in synthesis rate is created between the interior and exterior of the nickel-based metal precursor. As a result, a nickel-based metal precursor having internal pores can be obtained. Here, the nickel-based metal precursor refers to a precursor for obtaining a nickel-based lithium metal oxide.
[0114] In the first step, the pH of the mixture is adjusted, for example, to 11.6 to 11.9 or 11.7 to 11.8. In the second step, the pH of the mixture is adjusted to a range, for example, 10.8 to 11.7, 11 to 11.7, 11.2 to 11.6, or 11.3 to 11.6. The difference between the pH of the second step and the pH of the first step is approximately 0.1 to 1.5, 0.1 to 1.0, 0.1 to 0.8, 0.1 to 0.6, 0.1 to 0.5, 0.1 to 0.3, or 0.1 to 0.2. In this way, by reducing the pH of the second step to the aforementioned difference relative to the pH of the first step, the co-precipitation rate is changed, thereby creating a difference in synthesis rate between the inside and outside of the nickel-based metal precursor. As a result, a nickel-based metal precursor having internal pores can be obtained. Here, the nickel-based metal precursor refers to a precursor for obtaining nickel-based lithium metal oxide.
[0115] The stirring time of the first stage may vary depending on the pH conditions of the first stage, but is, for example, in the range of 8 to 12 hours or 9 to 10 hours.
[0116] In this invention, the co-precipitation reaction described above proceeds at a faster rate compared to general methods for manufacturing cathode active material precursors. This allows for high control of the pore dispersion of the core, enabling the cathode active material to be easily manufactured without a separate grinding process, thereby improving productivity. High control of pore dispersion results in a higher number of pores in the active material after heat treatment, causing the material to break easily during pressing, which in turn enables the cathode to exhibit excellent electrochemical properties. Here, proceeding with the co-precipitation reaction at a high rate is possible by increasing the stirring speed while keeping the stirring time short.
[0117] A metal precursor having internal pores comprises a secondary particle containing a plurality of primary particles, similar to a positive electrode active material, and has a hollow structure having internal pores. The size of the single particle is 10 to 18 μm. The size of the primary particle is 0.2 to 0.3 μm.
[0118] The nickel-based metal precursor having internal pores described above exhibits amorphous characteristics and contains an interior where pores exist and an exterior having a denser structure compared to the interior. The amorphous characteristics of the nickel-based metal precursor can be confirmed by X-ray diffraction analysis. In this specification, the “interior” of the nickel-based metal precursor refers to a pore region where a plurality of pores exist, and refers to the region excluding 50 to 70 volume%, for example 60 volume%, from the center of the total volume from the center to the surface of the precursor, or the region within 3 μm from the outermost edge of the cathode active material (exterior) among the total distance from the center to the surface of the precursor.
[0119] According to another embodiment, the interior of the nickel-based metal precursor is a porous region and represents a region with a major axis length of 2 μm to 7 μm, for example, 3.5 to 5 μm.
[0120] In a metal precursor having internal pores, the size of the pore region is 2 to 7 μm, and the size of the secondary particle is 10 to 15 μm, or 11 to 14 μm. When the size of the pore region and the size of the secondary particle of the metal precursor are within the above ranges, a positive electrode active material with excellent phase stability and improved capacitance characteristics can be obtained.
[0121] In this specification, the “pore area size” is primarily measured using the mercury intrusion method, the gas adsorption method, or SEM. Gas adsorption methods include the BET (Brunauer, Emmett, Teller) method or the BJH (Barrett-Joyner-Halenda) method. In this specification, pore size refers to the average pore size. In the embodiments of the present invention, pore size is measured using the BET method. The SEM method evaluates pore size using image analysis.
[0122] The above mixture may include complexing agents, pH adjusters, etc.
[0123] pH regulators play a role in lowering the solubility of metal ions inside the reactor, causing the metal ions to precipitate as hydroxides. Examples of pH regulators include ammonium hydroxide, sodium hydroxide (NaOH), and sodium carbonate (Na2CO3). An example of a pH regulator is sodium hydroxide (NaOH).
[0124] Complexing agents play a role in controlling the reaction rate of precipitate formation in co-precipitation reactions. Complexing agents include ammonium hydroxide (NH4OH) (ammonia water), citric acid, acrylic acid, tartaric acid, glycolic acid, etc. The content of the complexing agent is used at a conventional level. An example of a complexing agent is ammonia water.
[0125] The product obtained from the above co-precipitation reaction can be washed and then dried to obtain a desired nickel-based metal precursor. Here, drying is carried out under normal conditions.
[0126] One or more metal precursors selected from the aforementioned nickel precursor, M1 precursor, and M2 precursor include, for example, a nickel precursor, a manganese precursor, and a cobalt precursor. Alternatively, the metal precursor includes, for example, a nickel precursor, a cobalt precursor, and an aluminum precursor.
[0127] Examples of nickel precursors include Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O4·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, nickel salts of fatty acids, nickel halides, or combinations thereof. Manganese precursors include, for example, manganese oxides such as Mn2O3, MnO2, and Mn3O4, MnCO3, Mn(NO3)2, MnSO4, and MnSO4 . Examples include H2O, manganese acetate, manganese dicarboxylate salts, manganese citrate and manganese fatty acid salts, manganese oxyhydroxide, manganese chloride, and other manganese halides, or combinations thereof.
[0128] Examples of cobalt precursors include Co(OH)2, CoOOH, CoO, Co2O3, Co3O4, Co(OCOCH3)2·4H2O, CoCl2, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or combinations thereof.
[0129] Aluminum precursors include, for example, aluminum hydroxide, aluminum chloride, aluminum oxide, or combinations thereof.
[0130] In the M2 precursor described above, the precursor containing each element may be a salt, hydroxide, oxyhydroxide, halide, or combination thereof containing each element. Here, the salt containing the element described above may be, for example, one or more selected from sulfate, alkoxide, oxalate, phosphate, halide, oxyhalide, sulfide, oxide, peroxide, acetate, nitrate, carbonate, citrate, phthalate, and perchlorate containing the element described above.
[0131] The content of the nickel precursor and one or more metal precursors selected from the M1 precursor and M2 precursor is stoichiometrically controlled so that the desired nickel-based metal precursor is obtained.
[0132] The above nickel-based metal precursor is a compound represented by the following chemical formula 3, a compound represented by the chemical formula 4, or a combination thereof.
[0133] [Chemical Formula 3]
[0134] (Ni 1-x-y M1 x M2 y )(OH)2
[0135] In Chemical Formula 3, M1 is one or more elements selected from Co, Mn and Al, and
[0136] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0137] 0.95≤a≤1.1, 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, cases where x and y are both 0 are excluded, and
[0138] [Chemical Formula 4]
[0139] (Ni 1-x-y M1 x M2 y )O
[0140] In Chemical Formula 4, M1 is one or more elements selected from Co, Mn and Al, and
[0141] M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0142] 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, and cases where x and y are both 0 are excluded.
[0143] Nickel-based metal precursors are compounds represented, for example, by the compound of Chemical Formula 5, the compound of Chemical Formula 6, or a combination thereof.
[0144] [Chemical Formula 5]
[0145] Ni 1-x-y-z Co x M3 y M4 z (OH)2
[0146] In Chemical Formula 5, M3 is one or more elements selected from Mn and Al, and
[0147] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0148] 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y, and z are simultaneously 0 are excluded, and
[0149] [Chemical Formula 6]
[0150] (Ni 1-x-y-z Co x M3 y M4 z )O
[0151] In Chemical Formula 6, M3 is one or more elements selected from Mn and Al, and
[0152] M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0153] 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y and z are simultaneously 0 are excluded.
[0154] The above nickel-based metal precursor is, for example, a compound represented by Chemical Formula 7, a compound represented by Chemical Formula 8, or a combination thereof.
[0155] [Chemical Formula 7]
[0156] Ni 1-x-y-z Co x Mn y M4 z (OH)2
[0157] In Chemical Formula 7, M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zirconium (Zr), and aluminum, and
[0158] 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y, and z are simultaneously 0 are excluded, and
[0159] [Chemical Formula 8]
[0160] Li a (Ni 1-x-y-z Co x Al y M4 z )O
[0161] In Chemical Formula 8, M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and
[0162] 0.95≤a≤1.1, 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, and cases where x, y and z are simultaneously 0 are excluded.
[0163] Next, a mixture of a nickel-based metal precursor having internal pores and a lithium precursor is obtained.
[0164] The mixing ratio of the lithium precursor and the nickel-based metal precursor is stoichiometrically controlled to produce the desired cathode active material. A molybdenum precursor is added to the mixture, and then a first heat treatment is performed on the obtained mixture. Through the first heat treatment, phase transition and grain growth proceed.
[0165] Figures 1a and 1b show the cross-sectional structure of the product after the first heat treatment when manufacturing an anode active material according to one embodiment.
[0166] The primary heat treatment product may include a primary particle layer of up to two layers.
[0167] The primary heat treatment product (10) includes a hollow primary particle layer having a single-layer structure as can be seen in FIG. 1a. The hollow primary particle layer contains primary particles (11).
[0168] The primary heat treatment product may contain a hollow primary particle layer having a two-layer structure as shown in FIG. 1b. By having this structure, the breaking process during grinding can be easily achieved. In FIG. 1b, reference numerals (11a) and (11b) represent the first primary particle and the second primary particle, respectively, forming a primary particle layer of one layer and a primary particle layer of two layers.
[0169] A grinding process is performed on the primary heat treatment product to obtain a product in the state of fine single particles.
[0170] According to one embodiment, grinding is performed using a jet mill, a fin mill, an ACM milling machine, a disc mill, etc. Grinding is performed at, for example, 10,000 to 20,000 rpm, for example, 12,000 to 16,000 rpm. The stirring time for grinding varies depending on the grinding conditions, but is performed for, for example, 30 to 90 seconds, 40 to 80 seconds, or 50 to 60 seconds.
[0171] A disintegration process may be additionally performed prior to the grinding process of the primary heat treatment product. By undergoing this disintegration process, the hard cake-like product obtained after the primary heat treatment can be disintegrated into powder. By further performing the disintegration process in this manner, single particles with a uniform particle state can be obtained.
[0172] Crushing is carried out in a roll crusher at 100 to 300 rpm, 100 to 250 rpm, or 120 to 275 rpm. The gap of the roll crusher is 1 to 3 mm, 1.2 to 2.8 mm, or 1.5 mm. The stirring time for crushing varies depending on the crushing conditions, but is generally carried out for 10 to 60 seconds.
[0173] Molybdenum precursors include, for example, molybdenum hydroxide, molybdenum chloride, molybdenum oxide, ammonium molybdate, or combinations thereof.
[0174] Ammonium molybdate is, for example, ammonium heptamolybdate hydrate ((NH4)6Mo7O 24 ·4H2O) can be cited.
[0175] Next, a cobalt precursor is added to the above-mentioned product in the form of small single particles to obtain a mixture. The cobalt precursor is used to form a coating layer containing a cobalt compound placed on the surface of a nickel-based lithium metal oxide.
[0176] In this specification, “grinding” refers to a process in which secondary particles are formed by strong aggregation between primary particles, and a process is carried out using equipment such as a jet mill that applies a strong force (air pressure, mechanical pressure, etc.) to remove such strong aggregation.
[0177] A secondary heat treatment is performed on the mixture obtained according to the above process to produce a positive electrode active material in the state of small single particles according to one embodiment.
[0178] The above second heat treatment is performed at a lower temperature than the first heat treatment, and crystallinity is restored when the second heat treatment is performed. If the second heat treatment is performed at a higher temperature than the first heat treatment, it becomes difficult to obtain single particles with excellent phase stability. In addition, if the product obtained from the first heat treatment in the above manufacturing method undergoes a grinding process, it becomes difficult to obtain an anode active material having a hollow structure.
[0179] The nickel-based metal precursor and the lithium precursor can be mixed such that the Li / Me (metal excluding Li) molar ratio is 0.9 or more and less than 1.1, greater than 1.0 and less than 1.1, 1.01 to 1.05, or 1.02 to 1.04. This mixing step of the nickel-based metal precursor and the lithium precursor can be carried out in two steps rather than as a single step. Here, the mixing ratio of the nickel-based metal precursor and the lithium precursor is appropriately controlled so that the Li / Me (metal excluding Li) molar ratio in the cathode active material finally obtained through one or two steps can be within the range described above.
[0180] Lithium precursors include, for example, lithium hydroxide, lithium carbonate, lithium sulfate, lithium nitrate, or combinations thereof.
[0181] The above first heat treatment is carried out in an oxidizing gas atmosphere at 800°C to 1200°C, 830°C to 1150°C, 850°C to 1100°C, 850°C to 950°C, or 870°C to 920°C, and the second heat treatment is carried out in an oxidizing gas atmosphere at 600°C to 850°C, 600°C to 800°C, 650°C to 800°C, 700°C to 800°C, or 720°C to 790°C. When the first heat treatment and the second heat treatment are carried out under the above conditions, a high-density and long-life lithium secondary battery can be manufactured.
[0182] The first heat treatment time varies depending on the first heat treatment temperature, and is carried out for, for example, 8 to 20 hours.
[0183] The oxidizing gas atmosphere uses an oxidizing gas such as oxygen or air, for example, said oxidizing gas consists of 10 to 20 volume% of oxygen or air and 80 to 90 volume% of an inert gas.
[0184] The cobalt precursor used when forming a coating layer containing a cobalt compound may include a hydroxide, sulfate, alkoxide, oxalate, phosphate, halide, oxyhalide, sulfide, oxide, peroxide, acetate, nitrate, carbonate, citrate, phthalate, perchlorate, or a combination thereof. For example, the cobalt precursor may include one or more compounds selected from Co3O4, Co(OH)2, CoO, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, and Co(SO4)2·7H2O.
[0185] The content of the cobalt precursor is stoichiometrically controlled so that the content of the cobalt compound contained in the coating layer containing the cobalt compound is 0.1 to 5.0 mol% or 0.5 to 5.0 mol% based on the total content of the cathode active material.
[0186] The mixing of the nickel-based metal precursor and the lithium precursor can be performed by dry mixing and can be carried out using a mixer or the like. Dry mixing can be performed using milling. The milling conditions are not particularly limited, but can be performed so that there is almost no deformation, such as pulverization, of the precursor used as a starting material. The size of the lithium precursor mixed with the nickel-based metal precursor can be controlled in advance. The size (average particle size) of the lithium precursor is in the range of 5 to 15 μm, for example, about 10 μm. The required mixture can be obtained by milling the lithium precursor having such a size with the precursor at 300 to 3,000 rpm. If the internal temperature of the mixer rises above 30°C during the milling process, a cooling process may be performed to maintain the internal temperature of the mixer within the room temperature range (25°C).
[0187] Nickel-based metal precursors are, for example, Ni 0.92 Co 0.06 Mn 0.02 (OH)2, Ni 0.92 Co 0.05 Al 0.03 (OH)2, Ni 0.94 Co 0.03 Al 0.03 (OH)2, Ni 0.88 Co 0.06 Al 0.06 (OH)2, Ni 0.96 Co 0.02 Al 0.02 (OH)2, Ni 0.93 Co 0.04 Al 0.03 (OH)2, Ni 0.8 Co 0.15 Al 0.05 O2(OH) 2, Ni 0.75 Co 0.20 Al 0.05 (OH) 2, Ni 0.92 Co 0.05 Mn 0.03 (OH)2, Ni 0.94 Co 0.03 Mn 0.03 (OH)2, Ni 0.88 Co0.06 Mn 0.06 (OH)2, Ni 0.96 Co 0.02 Mn 0.02 (OH)2, Ni 0.93 Co 0.04 Mn 0.03 (OH)2, Ni 0.8 Co 0.15 Mn 0.05 (OH)2, Ni 0.75 Co 0.20 Mn 0.05 (OH)2, Ni 0.6 Co 0.2 Mn 0.2 (OH)2, Ni 0.7 Co 0.15 Mn 0.15 (OH)2, Ni 0.7 Co 0.1 Mn 0.2 (OH)2, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, or Ni 0.85 Co 0.1 Al 0.05 (OH)2
[0188] The nickel-based lithium metal oxide according to one embodiment is, for example, LiNi 0.92 Co 0.06 Mn 0.02 O2, Li 1.05 Ni 0.92 Co 0.05 Al 0.03 O2, Li 1.05 Ni 0.94 Co 0.03 Al 0.03 O2, Li 1.05 Ni 0.88 Co 0.06 Al 0.06 O2, Li 1.05 Ni 0.96 Co 0.02 Al 0.02 O2, Li 1.05 Ni 0.93 Co 0.04 Al 0.03 O2, Li 1.05 Ni 0.8 Co 0.15 Al 0.05 O2, Li 1.05 Ni 0.75 Co 0.20 Al 0.05 O 2, Li 1.05 Ni 0.92 Co 0.05 Mn 0.03 O2, Li 1.05 Ni 0.94 Co 0.03 Mn 0.03 O2, Li 1.05 Ni 0.88 Co 0.06 Mn 0.06 O2, Li 1.05 Ni 0.96 Co 0.02 Mn 0.02 O2, Li 1.05 Ni 0.93 Co 0.04 Mn 0.03 O2, Li 1.05 Ni 0.8 Co 0.15 Mn 0.05 O2, Li 1.05 Ni 0.75 Co 0.20 Mn 0.05 O2, Li 1.05 Ni 0.6 Co 0.2 Mn 0.2 O2, Li 1.05 Ni 0.7 Co 0.15 Mn 0.15 O2, Li 1.05 Ni 0.7 Co 0.1 Mn 0.2 O2, Li 1.05 Ni 0.8 Co 0.1 Mn 0.1 O2, or Li 1.05 Ni 0.85 Co 0.1 Al 0.05 It is O2.
[0189] According to another aspect, a positive electrode for a lithium secondary battery comprising a positive current collector and the positive active material described above is provided.
[0190] A lithium secondary battery according to another embodiment comprises the aforementioned positive electrode, negative electrode, and an electrolyte interposed between them.
[0191] By using the method for manufacturing a positive electrode active material according to one embodiment, a lithium secondary battery with improved discharge capacity and charge / discharge efficiency can be manufactured.
[0192] Hereinafter, a method for manufacturing a lithium secondary battery comprising a positive electrode, a negative electrode, a lithium salt-containing non-aqueous electrolyte, and a separator, including a positive electrode active material according to one embodiment, will be described.
[0193] The positive and negative electrodes are manufactured by forming the positive active material layer and the negative active material layer, respectively, by applying and drying a composition for forming the positive active material layer and a composition for forming the negative active material layer onto a current collector.
[0194] The above composition for forming the positive electrode active material is prepared by mixing a positive electrode active material, a conductive material, a binder, and a solvent, wherein a nickel-based active material according to one embodiment is used as the positive electrode active material.
[0195] The positive electrode binder serves to improve adhesion between positive electrode active material particles and adhesion between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one of these alone or a mixture of two or more may be used.
[0196] The above conductive material is not particularly limited as long as it possesses conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon nanotubes, carbon fibers, or metal fibers; fluorinated carbon; metal powders such as aluminum or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.
[0197] The content of the conductive material is used in an amount of 1 to 10 parts by weight or 1 to 5 parts by weight based on 100 parts by weight of the positive electrode active material. When the content of the conductive material is within the above range, the conductivity characteristics of the finally obtained electrode are excellent.
[0198] As a non-limiting example of the above solvent, N-methylpyrrolidone, etc., is used, and the solvent content is used in an amount of 20 to 200 parts by weight based on 100 parts by weight of the positive electrode active material. When the solvent content is in the above range, the process of forming the positive electrode active material layer is easy.
[0199] The above positive current collector has a thickness of 3 to 500 μm and is not particularly limited as long as it has high conductivity without causing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. The current collector may also form fine irregularities on its surface to increase the adhesion of the positive active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics are possible.
[0200] The positive current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. Since the base film includes a thermoplastic polymer, the base film may liquefy upon the occurrence of a short circuit, thereby suppressing a rapid increase in current. The base film may be, for example, an insulator. The metal layer may include, for example, indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive current collector (511b) may additionally include a metal piece and / or a lead tab. For more specific details regarding the base film, metal layer, metal piece, and lead tab of the positive current collector, refer to the description in the above-described negative current collector. By having this structure, the positive current collector can reduce the weight of the electrode and, consequently, improve energy density.
[0201] Separately, a composition for forming a negative electrode active material layer is prepared by mixing a negative electrode active material, a binder, and a solvent.
[0202] As the above-mentioned negative electrode active material, a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, a transition metal oxide, or a combination thereof may be used.
[0203] Examples of materials capable of reversibly intercalating / deintercalating the above lithium ions include carbon materials, namely carbon-based negative electrode active materials commonly used in lithium secondary batteries. Representative examples of carbon-based negative electrode active materials include crystalline carbon, amorphous carbon, or a combination thereof. Examples of the above crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the above amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.
[0204] As the above lithium metal alloy, an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.
[0205] Materials capable of doping and dedoping the above lithium include silicon-based materials, for example, Si, SiO xExamples include (0 < x < 2), Si-Q alloy (wherein Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, rare earth elements, and combinations thereof, and is not Si), Si-carbon complex, Sn, SnO2, Sn-R (wherein R is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, rare earth elements, and combinations thereof, and is not Sn), Sn-carbon complex, or combinations thereof, and at least one of these may be mixed with SiO2. For the above elements Q and R, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof may be used.
[0206] Lithium titanium oxide can be used as the above transition metal oxide.
[0207] The cathode binder may be various types of binder polymers, such as polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethylcellulose (CMC), starch, hydroxypropylcellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which the hydrogens thereof are substituted with Li, Na, or Ca, etc., or various copolymers.
[0208] The above-mentioned negative electrode active material layer may further include a thickener.
[0209] The above thickener may use at least one of carboxymethyl cellulose (CMC), carboxyethyl cellulose, starch, regenerated cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, and polyvinyl alcohol, and for example, CMC may be used.
[0210] The content of the above solvent is used in an amount of 100 to 300 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material. When the solvent content is within the above range, the process of forming the negative electrode active material layer is easy.
[0211] The above-mentioned negative electrode active material layer does not require a conductive material if conductivity is ensured. The negative electrode active material layer may further include a conductive material as needed. The above-mentioned conductive material is not particularly limited as long as it possesses conductivity without causing chemical changes in the battery, and for example, graphite such as natural graphite or artificial graphite; carbon black such as carbon black, acetylene black, Ketjen black, channel black, Farnes black, lamp black, thermal black; conductive fibers such as carbon fibers or metal fibers; conductive tubes such as carbon nanotubes; metal powders such as fluorocarbon, aluminum, or nickel powder; conductive whiskers such as zinc oxide or potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, etc., may be used. The above-mentioned conductive material may preferably be carbon black, and more specifically, may be carbon black having an average particle size of tens of nanometers.
[0212] When the negative electrode active material layer contains a conductive material, the content of the conductive material is 0.01 to 10 parts by weight, 0.01 to 5 parts by weight, or 0.1 to 2 parts by weight based on 100 parts by weight of the total weight of the negative electrode active material layer.
[0213] The above-mentioned negative current collector is generally made with a thickness of 3 to 500 μm. Such a negative current collector is not particularly limited as long as it is conductive without causing chemical changes in the battery, and for example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., and aluminum-cadmium alloy may be used. In addition, similar to the positive current collector, fine irregularities may be formed on the surface to strengthen the bonding strength of the negative active material, and it may be used in various forms such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabrics.
[0214] The above-described negative current collector may include, for example, a base film and a metal layer disposed on one or both sides of the base film. The base film may include, for example, a polymer. The polymer may be, for example, a thermoplastic polymer. The polymer may include, for example, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polybutylene terephthalate (PBT), polyimide (PI), or a combination thereof. Since the base film includes a thermoplastic polymer, the base film may liquefy upon the occurrence of a short circuit, thereby suppressing a rapid increase in current. The base film may be, for example, an insulator. The metal layer may include, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), or an alloy thereof. The metal layer may act as an electrochemical fuse and cut upon overcurrent to perform a short-circuit prevention function. The limit current and maximum current may be controlled by adjusting the thickness of the metal layer. The metal layer may be plated or deposited on the base film. As the thickness of the metal layer decreases, the limit current and / or maximum current of the negative current collector (521b, 522b) decreases, thereby improving the stability of the lithium battery during a short circuit. A lead tab may be added to the metal layer for external connection. The lead tab may be welded to the metal layer or the metal layer / base film laminate by ultrasonic welding, laser welding, spot welding, etc. During welding, the base film and / or the metal layer melt, allowing the metal layer to be electrically connected to the lead tab. To make the weld between the metal layer and the lead tab more robust, a metal ship may be added between the metal layer and the lead tab. The metal ship may be a thin sheet of the same material as the metal of the metal layer. The metal ship may be, for example, a metal foil, a metal mesh, etc.The metal chip may be, for example, aluminum foil, copper foil, SUS foil, etc. A lead tab may be welded to a metal chip / metal layer laminate or a metal chip / metal layer / base film laminate by placing the metal chip on the metal layer and then welding it to the lead tab. During welding, the base film, metal layer, and / or metal chip may melt, thereby electrically connecting the metal layer or the metal layer / metal chip laminate to the lead tab. A metal chip and / or lead tab may be added to a portion of the metal layer. The thickness of the base film may be, for example, 1 to 50 μm, 1.5 to 50 μm, 1.5 to 40 μm, or 1 to 30 μm. By having the base film within this thickness range, the weight of the electrode assembly can be reduced more effectively. The melting point of the base film may be, for example, 100 to 300 °C, 100 to 250 °C, or 100 to 200 °C. Since the base film has a melting point within this range, the base film can melt during the welding process of the lead tab and be easily bonded to the lead tab. Surface treatments, such as corona treatment, may be performed on the base film to improve the adhesion between the base film and the metal layer. The thickness of the metal layer may be, for example, 0.01 to 3 μm, 0.1 to 3 μm, or 0.1 to 2 μm. By having the metal layer within this thickness range, the stability of the electrode assembly can be ensured while maintaining conductivity. The thickness of the metal piece may be, for example, 2 to 10 μm, 2 to 7 μm, or 4 to 6 μm. By having the metal piece within this thickness range, the connection between the metal layer and the lead tab can be performed more easily. Since the negative current collector has this structure, the weight of the electrode can be reduced, and consequently, the energy density can be improved.
[0215] A separator is interposed between the anode and cathode produced according to the above process.
[0216] The above separator is used with a pore diameter of 0.01 to 10 μm and a thickness of generally 5 to 30 μm. Specific examples include olefin-based polymers such as polypropylene and polyethylene; or sheets or nonwoven fabrics made of glass fibers. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte may also serve as the separator.
[0217] Lithium salt-containing non-aqueous electrolytes consist of a non-aqueous electrolyte and a lithium salt. Non-aqueous electrolytes include non-aqueous electrolytes, organic solid electrolytes, and inorganic solid electrolytes.
[0218] As the above-mentioned non-aqueous electrolyte, non-limiting examples include N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, 2-methyl tetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolan, N,N-formamide, N,N-dimethylformamide, dioxolan, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphate triester, trimethoxymethane, dioxolan derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate, ethyl propionate, etc.
[0219] The above organic solid electrolyte may be used as, but is not limited to, examples such as polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate ester polymers, polyester sulfides, polyvinyl alcohol, polyvinylidene fluoride, etc.
[0220] As the above-mentioned inorganic solid electrolyte, non-limiting examples include Li nitrides, halides, sulfates, etc., such as Li3N, LiI, Li5NI2, Li3N-LiI-LiOH, LiSiO4, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.
[0221] The above lithium salt is a substance that dissolves well in the above-mentioned non-aqueous electrolyte, and is a non-limiting example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, (FSO2)2NLi, lithium chloroborate, or a combination thereof may be used.
[0222] FIG. 10 is a cross-sectional view schematically illustrating a representative structure of a lithium secondary battery according to one embodiment.
[0223] Referring to FIG. 10, the lithium secondary battery (41) includes a positive electrode (43), a negative electrode (42), and a separator (44) according to one embodiment. An electrode assembly in which the above-described positive electrode (43), negative electrode (42), and separator (44) are wound or folded is received in a battery case (45). Depending on the battery shape, a separator may be placed between the positive electrode and the negative electrode to form an alternately stacked battery structure. Subsequently, an organic electrolyte is injected into the battery case (45) and sealed with a cap assembly (46) to complete the lithium secondary battery (41). The battery case (45) may be cylindrical, prismatic, thin-film, etc. For example, the lithium secondary battery (41) may be a large thin-film battery. The lithium secondary battery may be a lithium-ion battery. After the battery structure is received in a pouch, it is impregnated with an organic electrolyte and sealed to complete the lithium-ion polymer battery. In addition, the above battery structure can be stacked in multiple units to form a battery pack, and such a battery pack can be used in any device requiring high capacity and high output. For example, it can be used in laptops, smartphones, electric vehicles, etc.
[0224] In addition, the above lithium secondary battery has excellent storage stability, lifespan characteristics, and high-rate characteristics at high temperatures, so it can be used in electric vehicles (EVs). For example, it can be used in hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs).
[0225] This will be explained in more detail through the following examples and comparative examples. However, the examples are for illustrative purposes only and are not limited thereto.
[0226] (Preparation of nickel-based metal precursors)
[0227] Preparation Example 1
[0228] nickel-based metal precursor (Ni) through the coprecipitation method 0.92 Co 0.06 Mn0.02 (OH)2) was synthesized.
[0229] Nickel sulfate (NiSO4) . 6H2O), cobalt sulfate (CoSO4 . 7H2O) and manganese sulfate (MnSO4 . A mixed metal raw material solution was prepared by dissolving (H2O) in distilled water, the solvent, so that the molar ratio of Ni:Co:Mn was 92:6:2. A diluted solution of ammonia water (NH4OH) and sodium hydroxide (NaOH) were prepared as a precipitating agent to form a complex compound. Subsequently, the above mixed metal raw material solution, ammonia water, and sodium hydroxide were each introduced into a reactor. Sodium hydroxide was added to maintain the pH inside the reactor.
[0230] After adjusting the pH of the mixture to 11.7 and stirring for 10 hours, the pH of the mixture is then adjusted to 11.5 to reduce the pH to about 0.2 relative to the initial pH, thereby changing the co-precipitation rate and creating a difference in synthesis rate between the inside and outside of the nickel-based metal precursor, so that a nickel-based metal precursor having internal pores can be obtained.
[0231] After carrying out the reaction for about 20 hours while stirring the above reaction mixture, the addition of the metal raw material mixture solution was stopped.
[0232] The slurry solution in the reactor is filtered, washed with high-purity distilled water, and dried in a hot air oven at 200°C for 24 hours to produce a nickel-based metal precursor (Ni) with a hollow structure having internal pores. 0.92 Co 0.06 Mn 0.02 (OH)2) was obtained. The nickel-based metal precursor is a secondary particle that is an aggregate of primary particles, and the average particle size of the secondary particles is about 14 μm.
[0233] (Manufacture of cathode active material for lithium secondary batteries)
[0234] Example 1: Co coating (2 mol%) and Mo doping (0.1 mol%)
[0235] Nickel-based metal precursor having a hollow structure of Preparation Example 1 (Ni 0.92Co 0.06 Mn 0.02 A first mixture was obtained by adding (OH)2)) and lithium carbonate. In the first mixture, the molar ratio of lithium to metal (Li / M) is approximately 1.04. Here, the metal content is the total content of Ni, Co, and Mn. To the first mixture, ammonium heptamolybdate hydrate ((NH4)6Mo7O 24 After adding ·4H2O), the mixture was subjected to a first heat treatment at 900°C for 15 hours in an air atmosphere. The content of ammonium heptamolybdate hydrate was controlled so that the content of molybdenum doped in the cathode active material was 0.1 mol%.
[0236] The product of the first heat treatment is milled in a Hosokawa jet mill (Blower 35Hz, AFG 8000rpm, Air 4 kgf / cm² 2 Grinding was performed using ) to produce a fine-grained product having a particle size of 3 to 4 μm after grinding.
[0237] According to the above process, the product after grinding is subjected to a second heat treatment at approximately 770°C in an oxygen atmosphere, Co(OH)2, a cobalt precursor, is added thereto, and a second heat treatment is performed at approximately 770°C in an oxygen atmosphere to obtain an anode active material (LiNi) having a hollow structure and containing a cobalt compound-containing coating layer. 0.899 Co 0.08 Mn 0.02 Mo 0.001 O2) was prepared in a single-particle state. The content of the molybdenum precursor was controlled so that the molybdenum content in the positive electrode active material was about 0.1 mol% based on 100 mol% of the total metal content excluding lithium. And the content of the cobalt precursor was controlled so that the cobalt compound content in the cobalt compound-containing coating layer was 2 mol% based on the total content of the positive electrode active material.
[0238] The positive active material obtained according to Example 1 is LiNi 0.899 Co 0.08 Mn 0.02 Mo 0.001It showed the O2 single particle state. The content of the cobalt compound is 2 mol% based on the total content of the finally obtained cathode active material, and the thickness of the coating layer is about 20 nm.
[0239] Example 2: Co coating (2 mol%) and Mo doping (0.2 mol%)
[0240] A lithium secondary battery cathode active material LiNi was prepared in the same manner as Example 1, except that the content of the molybdenum precursor was controlled to be approximately 0.2 mol% based on 100 mol% of the total metal content excluding lithium in the cathode active material. 0.898 Co 0.08 Mn 0.02 Mo 0.002 O2 was manufactured.
[0241] Example 3: Co coating (2 mol%) and Mo doping (0.4 mol%)
[0242] Except for the fact that the content of the cobalt precursor is controlled so that the content of the cobalt compound in the cobalt compound-containing coating layer is 2 mol% based on the total content of the cathode active material, and the content of the molybdenum precursor is controlled so that it is approximately 0.4 mol% based on 100 mol% of the total metal content excluding lithium in the cathode active material, the cathode active material LiNi for a lithium secondary battery 0.896 Co 0.08 Mn 0.02 Mo 0.004 O2 was manufactured.
[0243] Reference Example 1: Co coating (2 mol%) and Mo undoped
[0244] A positive electrode active material for a lithium secondary battery was prepared in the same manner as in Example 1, except that the process of adding ammonium heptamolybdate hydrate to the first mixture was not performed.
[0245] Reference Example 2: Co coating (2 mol%) and Mo doping (1.0 mol%)
[0246] A positive electrode active material for a lithium secondary battery was prepared in the same manner as in Example 1, except that the content of ammonium heptamolybdate hydrate added to the first mixture was controlled so that the content of molybdenum doped in the positive electrode active material was 1.0 mol%.
[0247] (Manufacturing of coin cells)
[0248] Production Example 1
[0249] A coin cell was manufactured as follows without a separate grinding process using the positive active material obtained according to Example 1 as the positive active material.
[0250] Nickel-based active material (LiNi obtained according to Example 1) 0.92 Co 0.06 Mn 0.02 A mixture of 96g of O2, 2g of polyvinylidene fluoride (PVdF, Solef 6020 (Solvey company), 47g of N-methylpyrrolidone as a solvent, and 2g of carbon black as a conductive agent was mixed using a mixer to remove bubbles and prepare a slurry for forming a uniformly dispersed positive electrode active material layer.
[0251] The slurry prepared according to the above process was coated onto an aluminum foil using a doctor blade to form a thin electrode plate, then dried at 135°C for more than 3 hours, and then the anode was produced through a pressing and vacuum drying process.
[0252] A 2032 type coin cell was manufactured using the above positive electrode and a lithium metal counter electrode as the counter electrode. A separator (thickness: approximately 16 μm) made of a porous polyethylene (PE) film was interposed between the above positive electrode and the lithium metal counter electrode, and an electrolyte was injected to fabricate the 2032 type coin cell. As the electrolyte, a solution containing 1.15 M LiPF6 dissolved in a solvent mixed with ethylene carbonate (EC), ethyl methyl carbonate (EMC), and DMC in a volume ratio of 20:40:40 was used. Vinylene carbonate was added to the electrolyte. The content of vinylene carbonate is 1.5 wt% based on 100 wt% of the electrolyte.
[0253] Production Examples 2 and 3: Coin Cell Manufacturing
[0254] A coin cell was manufactured by following the same method as in Example 1, except that the positive active materials of Example 2 and Example 3 were used instead of the positive active material of Example 1.
[0255] Reference Production Example 1 and Reference Production Example 2: Coin Cell Manufacturing
[0256] A coin cell was manufactured in the same manner as in Example 1, except that the positive active material obtained according to Reference Example 1 and Reference Example 2 was used as the positive active material, respectively.
[0257] Evaluation Example 1: Scanning Electron Microscope Analysis I
[0258] Scanning electron microscope analysis was performed on the surface of the secondary particles of the positive electrode active materials of Example 1, Example 3, and Reference Example 1. A Magellan 400L (FEI company) was used for the scanning electron microscope, and the analysis results of the products after the first heat treatment during the preparation of the positive electrode active materials of Examples 1-3 and Reference Example 1 are shown in Figs. 2a, 2b, 2c, 3a, 3b, 3c, 4a, 4b, 4c, 5a, 5b, and 5c. In addition, the analysis results of the products after the second heat treatment during the preparation of the positive electrode active materials of Examples 1-3 and Reference Example 1 are shown in Figs. 2d, 2e, 3d, 3e, 4d, 4e, 5d, and 5e. Here, FIGS. 2a to 2e relate to the positive active material of Example 1, FIGS. 3a to 3e relate to the positive active material of Example 2, FIGS. 4a to 4e relate to the positive active material of Example 3, and FIGS. 5a to 5e relate to the positive active material of Reference Example 1.
[0259] It was found that for each of Examples 1 to 3 and Reference Example 1, after the first heat treatment, a large particle having a hollow structure was obtained as shown in FIGS. 2a to 2c, FIGS. 3a to 3c, FIGS. 4a to 4c, and FIGS. 5a to 5c, and after making this large particle into a small particle through grinding and then proceeding with a second heat treatment, a final small particle (images corresponding to each d~e) was produced as shown in FIGS. 2d-2e, FIGS. 3d-3e, FIGS. 4d-4e, and FIGS. 5d-5e.
[0260] Evaluation Example 2: Scanning Electron Microscopy Analysis II
[0261] Scanning electron microscope analysis was performed on the nickel-based metal precursor of Preparation Example 1, and the results of the analysis are shown in Fig. 6.
[0262] Referring to this, the nickel-based metal precursor of Preparation Example 1 contained secondary particles having internal pores and a size of 14 μm. The internal area containing the pores had a major axis length of approximately 5.76 μm and exhibited an amorphous structure.
[0263] In addition, scanning electron microscope analysis was performed on the cross-section of the secondary particles of the positive electrode active material of Example 1. A Magellan 400L (FEI company) was used for the scanning electron microscope, and the analysis results are shown in Fig. 1c.
[0264] Figure 1c is an SEM image of a cross-section of the positive electrode active material of Example 1.
[0265] Referring to Fig. 1c, the positive active material of Example 1 was composed of single particles with a size of 3.0 μm.
[0266] Evaluation Example 3: Particle Size Distribution Characteristics
[0267] The particle size distribution characteristics of the cathode active materials of Examples 1 to 3 and Reference Example 1 were analyzed using a PSA (Particle Size Analyzer). The analysis results are shown in Table 1 and Figure 7 below.
[0268] In Table 1 below, span is represented as (D90-D10) / D50.
[0269] The above particle size distribution graph can be obtained under the following PSD measurement conditions.
[0270] An LS13320 (Beckmann Coulter) was used as a laser particle size analyzer, and the analysis conditions were as follows.
[0271] Pump speed (55%), Sample ultrasonic dispersion 40 KHz ultrasound (60s), Run Length 60s, Refractive Index Ratio Sample RI 1.6, e-factor 1.00, Sample volume 0.20g, Sample input dispersant: 10% Sodium Hexamethaphosphate 1 ml
[0272] Mo content Powder characteristics Particle size distribution (㎛) mol% D10 D50 D90 Span. Example 1 0.1 1.84 3.00 4.77 0.98 Example 2 0.2 1.76 2.86 4.60 1.00 Example 3 0.4 1.50 2.56 4.22 1.06 Reference Example 1 0 1.90 3.01 4.63 0.91
[0273] Referring to Table 1 and Figure 7, it was found that the positive active materials of Examples 1 to 3 had a span of less than 1.1, indicating uniform particle size. Furthermore, it was observed that the positive active materials of Examples 1-3 and Reference Example 1 were all products with uniform particles, and that the size of the positive active material decreased slightly as the molybdenum (Mo) content increased. Additionally, the average particle size of the positive active materials of Examples 1 to 3 and Reference Example 1 was analyzed using a scanning electron microscope. During the analysis, the average particle size was determined as the average value of at least 30 randomly extracted particles of 1 μm or larger, excluding fine particles, using a scanning electron microscope.
[0274] As a result, the average particle size of the positive active materials of Examples 1 to 3 and the positive active material of Reference Example 1 showed results similar to D50 of Table 1 above.
[0275] Evaluation Example 4: X-ray Diffraction Analysis
[0276] X-ray diffraction analysis was performed on the cathode active materials prepared according to Examples 1 to 3 and Reference Example 1 using X'pert pro (PANalytical) with Cu Kα radiation (1.54056 Å), and the results are shown in Table 2 below.
[0277] FWHM in Table 3 below (003) represents the full width at half maximum (FWHM) of the peak corresponding to the (003) plane (the peak where 2θ is approximately 18-19°), and FWHM (104) represents the half-width of the peak corresponding to the (104) plane (the peak where 2θ is approximately 44.5°).
[0278] division FWHM (003) (°) FWHM (104) (°) FWHM (003) / FWHM (104) Example 1 0.0910 0.1198 0.76 Example 2 0.0897 0.1226 0.73 Example 3 0.0932 0.1214 0.77 Reference Example 1 0.0878 0.1098 0.80
[0279] The positive active materials of Examples 1 to 3 are FWHM(003) and FWHM of Table 2. (003) / FWHM (104) It was found that it was a single particle from the characteristics. In addition, it was found that the positive active materials of Examples 1 to 3 had excellent crystal characteristics with minimal crystal damage after undergoing a secondary heat treatment even after a grinding process. The minimal crystal damage of the positive active material can be confirmed from the above-mentioned FWHM (003) and FWHM (003) / FWHM (104) values. A lower FWHM (003) indicates that the crystal grains of the active material have grown into a large and uniform crystal structure in the (003) direction, and a higher FWHM (003) / FWHM (104) ratio indicates that they have also grown into a large and uniform crystal structure in the (104) direction.
[0280] As can be seen from Table 2, the positive active materials of Examples 1 to 3 exhibited excellent crystallinity similar to that of the positive active material of Reference Example 1.
[0281] Evaluation Example 5: Residual Lithium
[0282] The residual lithium characteristics of the cathode active materials of Examples 1 to 3 and Reference Example 1 were evaluated, and the evaluation results are shown in Table 3 below.
[0283] The residual lithium content was measured by acid-base titration. 50 g of the prepared active material was added to a beaker along with 100 ml of ultrapure water and stirred. The stirred solution was then separated into solution and powder using filter paper, and the pH of the resulting solution was determined by performing pH titration with 0.1 N hydrochloric acid. The content of lithium hydroxide and lithium carbonate was measured and is shown in Table 3 below.
[0284] Mo Residual lithium mol% Li2CO3 LiOH Free Li Example 1 0.1 0.889 0.258 2419 Example 2 0.2 0.832 0.397 2716 Example 3 0.4 0.754 0.725 3521 Reference Example 1 0 0.797 0.223 2146
[0285] From Table 3, it was found that the cathode active materials of Examples 1 to 3 had a low residual lithium content, similar to the case of Reference Example 1.
[0286] Evaluation Example 6: Room Temperature Charge / Discharge Characteristics
[0287] In the coin cells manufactured according to Manufacturing Examples 1 to 3, Reference Manufacturing Example 1 and Reference Manufacturing Example 2, the charge and discharge characteristics, etc. were evaluated using a charge / discharger (Manufacturer: TOYO, Model: TOYO-3100).
[0288] The first charge / discharge was performed at 25°C with a constant current of 0.1C until 4.25V was reached, followed by constant voltage charging until 0.05C was reached. After the charging was complete, the cell was allowed to rest for about 10 minutes, and then constant current discharge was performed with a current of 0.1C until the voltage reached 3V.
[0289] The second charge / discharge cycle was performed by charging with a constant current of 0.2C until it reached 4.25V, followed by charging with a constant voltage of 0.05C until it reached 0.05C. After the charging was complete, the cell was rested for about 10 minutes, and then discharged with a constant current of 0.2C until the voltage reached 3V.
[0290] For the life evaluation, constant current charging was performed at 1C until the voltage reached 4.25 V, followed by constant voltage charging until the voltage reached 0.05C. After the charging was complete, the cell was evaluated by repeating a cycle of constant current discharge at 1C until the voltage reached 3 V 50 times, after a rest period of about 10 minutes.
[0291] The charge / discharge efficiency was calculated from Equation 1.
[0292] [Equation 1]
[0293] Charge / Discharge Efficiency = [0.2C Discharge Voltage / 0.2C Charge Voltage] × 100
[0294] The charge / discharge efficiency described above was evaluated and is shown in Table 4 below, the change in capacity according to voltage was investigated and is shown in Fig. 8a, and the difference in resistance during initial charging was investigated and is shown in Fig. 8b.
[0295] division 0.2C charging 0.2C discharge Charge / Discharge Efficiency (%) Production Example 1 238.08 215.97 90.7 Production Example 2 237.94 216.99 91.2 Production Example 3 237.17 217.86 91.9 Reference Production Example 1 236.91 212.47 89.7 Reference Production Example 2 238.90 210.74 88.2
[0296] Referring to Table 4, Fig. 8a, and Fig. 8b, it was found that the charge / discharge efficiency of the coin cells manufactured according to Examples 1 to 3 was improved compared to the cases of Reference Examples 1 and 2. Additionally, referring to Fig. 8b, it was found that the initial resistance decreased as the molybdenum (Mo) content increased.
[0297] Evaluation Example 7: High-temperature charge / discharge characteristics
[0298] In the coin cells manufactured according to Manufacturing Examples 1 to 3, Reference Manufacturing Example 1 and Reference Manufacturing Example 2, the charge and discharge characteristics, etc. were evaluated using a charge / discharger (Manufacturer: TOYO, Model: TOYO-3100).
[0299] The first charge / discharge was performed at 45°C with a constant current of 0.1C until 4.3V was reached, followed by constant voltage charging until 0.05C was reached. After the charging was complete, the cell was allowed to rest for about 10 minutes, and then constant current discharge was performed with a current of 0.1C until the voltage reached 3V.
[0300] The second charge / discharge cycle involved constant current charging at 0.2C until 4.3V was reached, followed by constant voltage charging at 0.05C until 0.05C was reached. After the charging was complete, the cell was allowed to rest for about 10 minutes, and then constant current discharge was performed at 0.2C until the voltage reached 3V.
[0301] For the life evaluation, constant current charging was performed at 1C until 4.3 V was reached, followed by constant voltage charging until 0.05C was reached. After the charging was complete, the cell was evaluated by repeating a cycle of constant current discharge at 1C until the voltage reached 3 V 50 times, after a rest period of about 10 minutes.
[0302] The capacity retention ratio (CRR) was calculated from Equation 2 below.
[0303] [Equation 2]
[0304] Capacity retention rate[%] = [50 th Discharge capacity per cycle / 1 st [Discharge capacity per cycle] x 100
[0305] Referring to FIG. 9, the coin cells manufactured according to Production Examples 1 to 3 exhibited an excellent capacity retention rate equivalent to that of the coin cells of Reference Production Example 1-2.
[0306] Although one embodiment has been described above with reference to the drawings and examples, this is merely illustrative, and those skilled in the art will understand that various modifications and equivalent alternative embodiments are possible therefrom. Accordingly, the scope of protection of the present invention should be determined by the appended claims. Explanation of the symbols
[0307] 41: Lithium battery 42: Negative electrode 43: Anode 44: Separator 45: Battery case 46: Cap assembly
Claims
Claim 1 A nickel-based lithium metal oxide single particle, wherein the single particle comprises a secondary particle containing a plurality of primary particles, and is a positive electrode active material for a lithium secondary battery having a hollow structure having pores inside, wherein the size of the primary particle is 0.2 to 0.3 μm, and the FWHM measured by X-ray diffraction analysis of the positive electrode active material (003) / FWHM (104) is 0.72 to 0.79, and FWHM measured by X-ray diffraction analysis of the anode active material (003) A positive electrode active material for a lithium secondary battery having a polarity of 0.089° to 0.094°. Claim 2 delete Claim 3 In claim 1, the FWHM measured by X-ray diffraction analysis of the positive electrode active material (104) A positive electrode active material for a lithium secondary battery having a polarity of 0.11° to 0.13°. Claim 4 A positive electrode active material for a lithium secondary battery in which molybdenum is doped into the nickel-based lithium metal oxide single particle according to claim 1. Claim 5 In paragraph 4, the content of molybdenum is 0.1 mol% or more and less than 1.0 mol% based on 100 mol% of the total metal content excluding lithium in the positive active material for a lithium secondary battery. Claim 6 A positive electrode active material for a lithium secondary battery comprising a cobalt compound-containing coating layer disposed on the surface of the nickel-based lithium metal oxide single particle in claim 1. Claim 7 A positive electrode active material for a lithium secondary battery according to claim 6, wherein the content of the cobalt compound in the cobalt compound-containing coating layer is 0.1 to 5.0 mol% based on the total content of the positive electrode active material. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 6, wherein the thickness of the cobalt compound-containing coating layer is 1 nm to 50 nm. Claim 9 In claim 6, the cobalt compound in the above-mentioned cobalt compound-containing coating layer is a positive electrode active material for a lithium secondary battery, which is cobalt oxide, lithium cobalt oxide, or a combination thereof. Claim 10 In claim 6, the above-mentioned cobalt compound-containing coating layer further comprises one or more selected from boron, manganese, phosphorus, aluminum, zinc, zirconium, and titanium, a positive electrode active material for a lithium secondary battery. Claim 11 In claim 1, the nickel-based lithium metal oxide is a compound represented by the following chemical formula 1, a positive electrode active material for a lithium secondary battery: [Chemical Formula 1]Li a (Ni 1-x-y M1 x M2 y )O 2±α1 In Chemical Formula 1, M1 is one or more elements selected from Co, Mn and Al, and M2 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), and zirconium (Zr), and 0.95≤a≤1.1, 0.6≤(1-xy)<1, 0≤x<0.4, 0≤y<0.4, 0≤α1≤0.1, and cases where x and y are simultaneously 0 are excluded. Claim 12 In claim 1, the nickel-based lithium metal oxide is a compound represented by the following chemical formula 2, a positive electrode active material for a lithium secondary battery: [Chemical Formula 2]Li a (Ni 1-x-y-z Co x M3 y M4 z )O 2±α1 In Chemical Formula 2, M3 is one or more elements selected from Mn and Al, and M4 is one or more elements selected from the group consisting of boron (B), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu) and zirconium (Zr), and 0.95≤a≤1.1, 0.6≤(1-xyz)<1, 0≤x<0.4, 0≤y<0.4, 0≤z<0.4, 0≤α1≤0.1, and cases where x, y and z are simultaneously 0 are excluded. Claim 13 A positive electrode for a lithium secondary battery comprising a positive current collector and a positive active material layer disposed on the positive current collector, wherein the positive active material layer comprises a positive active material of any one of claims 1, 3 to 12. Claim 14 A lithium secondary battery comprising the positive electrode of claim 13; the negative electrode; and an electrolyte interposed between them.
Citation Information
Patent Citations
Cathode active material for lithium secondary battery, preparing method thereof, cathode for lithium secondary battery including the same, and lithium secondary battery comprising cathode including the same
KR1020230002065A
Positive active material for rechargeable lithium battery, preparing method thereof and rechargeable lithium battery including the same
KR1020230025342A
Positive active material for rechargeable lithium battery, preparing method thereof and rechargeable lithium battery including the same
KR1020220160919A
Cathode active material for lithium secondary battery, preparing method thereof, cathode for lithium secondary battery including the same, and lithium secondary battery comprising cathode including the same
KR1020230026841A